Cytotoxicity of the essential oil of Fennel (Foeniculum vulgare) from Tajikistan - Sharopov, Farukh; Wink, Michael (Foods, 2017)
The essential oil of fennel (Foeniculum vulgare) is rich in lipophilic secondary metabolites, which can easily cross cell membranes by free diffusion. Several constituents of the oil carry reactive carbonyl groups in their ring structures. Carbonyl groups can react with amino groups of amino acid residues in proteins or in nucleotides of DNA to form Schiff’s bases. Fennel essential oil is rich in anise aldehyde, which should interfere with molecular targets in cells. The aim of the present study was to investigate the chemical composition of the essential oil of fennel growing in Tajikistan. Gas chromatographic-mass spectrometric analysis revealed that the main components of F. vulgare oil were trans-anethole (36.8%); α-ethyl-p-methoxy-benzyl alcohol (9.1%); p-anisaldehyde (7.7%); carvone (4.9%); 1-phenyl-penta-2,4-diyne (4.8%) and fenchyl butanoate (4.2%). The oil exhibited moderate antioxidant activities. The potential cytotoxic activity was studied against HeLa (human cervical cancer), Caco-2 (human colorectal adenocarcinoma), MCF-7 (human breast adenocarcinoma), CCRF-CEM (human T lymphoblast leukaemia) and CEM/ADR5000 (adriamycin resistant leukaemia) cancer cell lines; IC50 values were between 30-210 mg L−1 and thus exhibited low cytotoxicity as compared to cytotoxic reference compounds.